Outlines of Russian culture - by Paul Miliukov. Edited by Michael Karpovich; translated by Valentine Ughet and Eleanor Davis. (University of Pennsylvania Press, 1948)
"An authorized abridged version of the original, specially prepared for the American edition."--Editor's foreword. I. Religion and the church.--II. Literature.--III. Architecture, painting, and music.